Investigation into students’ performance in foreign language business writing and their attitudes toward it - Thaksanan, Piriya (Universitas Ahmad Dahlan, 2024)
Anxiety can affect learners' performance in several ways. It can be a helpful motivational tool to assist students in learning a language. At the same time, anxiety can become a serious factor in hindering language acquisition. This study examines the relationship between students' writing performance and anxiety levels across three different proficiency groups of students. The participants were fifty EFL students enrolled in a Business English Writing course, and the target writing genre was inquiries and acknowledgments of inquiry letters. The two main instruments used to collect data were students' writing samples and closed-ended questionnaires. The data were analyzed utilizing descriptive statistics, one-way ANOVA, and Pearson's coefficient correlation. This study showed a significant difference in writing anxiety between the high and the low-proficiency groups. In contrast, it was found that there were no statistically significant differences in anxiety between the high and the mid-proficiency groups. In addition, the study’s outcomes indicated that the students' level of anxiety varied across the three groups of students. It was found that the students with a high level of anxiety performed less well than those with lower writing anxiety. The findings provide insights into teaching and learning writing, particularly into ways to decrease learners' anxiety and improve their learning outcomes.